Getting Personal in Supreme Court Opinions - Joseph L. Smith (Washington University Journal of Law & Policy, 2017)
This Article reviews recent Supreme Court decisions to identify instances in which justices have directly targeted and criticized opposing opinions of other justices by name. Smith notes there was a dramatic increase in average persona referenced to other justices per opinion during the Rehnquist and Roberts Courts, with many justices referring to fellow justices by name when they are ideological opposites and rarely if when the target justice is a swing vote in a decision. Smith concludes that frayed relationships on the bench may continue if justices feel free to personally reference other justices of opposing ideological beliefs and the Court continues its ideological polarization.
Keywords: Supreme Court; Opinion; Roberts Court; Ideology; Personal Relationships; Study